Attitudes towards and health consequences of female genital mutilation/cutting: A qualitative study among Somali and Kurdish immigrants and descendants in Denmark - Ditte S. Linde; Hawa-Idil Harakow; Negin Jaafar (Elsevier, 2024)
Objectives: There is lack of in-depth knowledge of how immigrants who originate from countries where female genital mutilation/cutting (FGM/C) historically is practiced, perceive the practice after migrating to Europe. The aim of this study was to explore the attitude towards FGM/C among immigrants and descendants and the health consequences of living with FGM/C. Study design: Qualitative methods were used in the form of semi-structured interviews and focus group discussions. Female and male immigrants and descendants in Denmark from Somalia or Kurdish of Iraq/Iran participated in the study. The interview/focus group discussion guides were developed by the European Institute for Gender Equality. Purposely sampling was used, and participants were recruited by use of snowballing through gatekeepers and women's societies working within the Somali and Kurdish communities. Results: Sixteen persons participated in the study. No descendants had been cut, but all female immigrants had been cut prior to migrating and did not wish to pass on the practice. FGM/C was perceived as a harmful practice with severe sexual and mental health consequences. Women with Somali origin experienced that the practice was falsely associated with their origin, which led to stigmatisation. Women with Kurdish origin lacked healthcare support when suffering sexual consequences of FGM/C. It was generally perceived that the Danish healthcare system lacked cultural sensitivity. Conclusion: FGM/C is negatively perceived among Somali and Kurdish immigrants and descendants in Denmark and not practiced among these groups. The Danish healthcare system should adopt a more culturally sensitive approach when addressing sexual health among immigrants and descendants. Denmark and other European countries should work towards destigmatising the immigrant communities when it comes to FGM/C. Larger European studies with primary data are needed to generalise the findings of this study.